Development of EKSIS (ebook ekosistem) to introduce the ecosystem concept in class 3 elementary school - Rucita Ayu Wijaksana; Ani Nur Aeni; Dety Amelia Karlina (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study aims to develop and validate the EKSIS product, a learning media based on ecosystem materials designed to introduce the concept of ecosystems to third-grade elementary school students. The research method used is Design and Development (D&D), with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation instrument consists of a five-point Likert scale assessment sheet to measure the quality of the product from two main aspects: product design and content material. The validation results show that EKSIS received an average score of 5 for both assessed aspects, placing it in the "excellent" category. The product was deemed relevant to learning needs, supported curriculum achievements, and had an effective design that engaged students and enhanced their understanding of ecosystem materials. Based on these findings, EKSIS is considered suitable for use in the learning process. The use of this product is expected to help introduce the concept of ecosystems and provide an engaging and in-depth learning experience for students. This research significantly contributes to developing innovative learning media that align with educational needs in the digital era.